Worldwide Research Trends on Transvenous Embolization of Brain Arteriovenous Malformations: A Bibliometric and Visualized Study - Saal-Zapata, Giancarlo (2023)
Background: Transvenous embolization (TVE) of brain arteriovenous malformations (bAVMs) is an emerging endovascular technique that has shown high cure rates in selected cases. The rationale of our study was to determine authorship and worldwide institutional trends and contributions to the knowledge in this topic. Methods: Web of Science database was used. A total of 63 articles were included based on predefined inclusion criteria, which were manually reviewed. The bibliometric analysis involved the use of quantitative bibliometric indicators and network analysis with co-authorship and co-occurrence of terms, which were performed using the bibliometrix package in R and VOSviewer, respectively. Results: The first article was published in 2010, with the largest number of articles published in 2022 (10 articles). The average number of citations per document was 11.38, and the annual growth rate was 14.35%. The top 10 authors with the most scientific production on TVE of bAVMs were from France, and the most cited study was published by Iosif C in 2015, followed by Consoli A in 2013, and Chen CJ in 2018. Journal of Neurointerventional Surgery was the journal with the most articles published. The most commonly used keywords were dural arteriovenous fistula, Onyx, vascular disorders, and neurological surgery around 2016, and intervention around 2021. Conclusions: TVE of bAVMs is an emerging technique. Our search identified some scientific articles, without randomized clinical trials, but many case series from single institutions. French and German institutions are the pioneers in the field, and further research is required in specialized endovascular centers.